Pengaruh Partisipasi Dalam Penganggaran dan Peran Manajerial Pengelola Keuangan Daerah Terhadap Kinerja Pemerintah Daerah: (Studi Empiris pada Pemerintah Kabupaten Probolinggo) - Hendra, Joni (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2018)
Factors influencing the performance of local government according to Abdul Halim (2007) are four, namely, entrepreneurial management capacity, organizational culture, macro environment and regional endowment, all of which demand for immediate reinventing local government. Probolinggo District Government performance performance is on performance performance of larger institution when compared with the realization of its expenditure.This study aims to determine the extent of the influence of participation in budgeting and managerial roles of local financial managers to the performance of the local government of Probolingggo.A sample of 82 samples were obtained from questionnaires distributed to 103 respondents consisting of 3 heads of bodies, 11 heads of service, 1 head of inspectorate, 1 secretary of parliament, 8 heads of office, 12 heads of department, 1 director of RSUD, 10 sub-district heads, 25 village heads and 31 principals of kindergarten / junior high / high school / vocational school in Probolinggo district government selected by using purposive sampling method. Of the 103 questionnaires submitted, 85 respondents returned and only 82 questionnaires could be processed and analyzed.The results showed that the high performance of local governments influenced participation in budgeting, meaning that the higher participation in budgeting will increase the performance of local government. The high performance of local government is influenced by the managerial role of regional financial manager means that the higher managerial role of regional finance manager will increase the performance of local government. The results of this study support previous studies and based on the underlying theory of agency theory and prospect theory.